2016
DOI: 10.5173/ceju.2016.830
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiogenesis in urothelial bladder carcinoma

Abstract: IntroductionBladder cancer is the most common urinary tract malignancy in western countries. In recent years, extensive research has suggested that angiogenesis plays an important role in bladder cancer biology, contributing to tumor growth and progression.Material and methodsIn this review, we discuss general mechanisms of angiogenesis and highlight the influence of pro- and anti-angiogenic factors, and cancer stem cells on bladder cancer biology, their relation to disease progression, and potential use in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 33 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…Angiogenesis is one of the most important factors in BCa progression 16 . BCa cells in tumor tissue may affect the vascular endothelium and therefore the interaction between BCa cells and microvascular endothelial cells via angiogenesis-related cytokines that play a crucial role in disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is one of the most important factors in BCa progression 16 . BCa cells in tumor tissue may affect the vascular endothelium and therefore the interaction between BCa cells and microvascular endothelial cells via angiogenesis-related cytokines that play a crucial role in disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of neovasculature through angiogenic processes is vital for cancer cell proliferation and tumor progression to metastasis (168). Historically, tumor angiogenesis was perceived as being primarily regulated by cancer cells expressing proangiogenic factors; however, now it becomes increasingly clear that the tumor microenvironment is a key factor inducing and sustaining chronic angiogenesis, including in a glycosylation-dependent manner.…”
Section: Tumor Microenvironment and Glycosylation Crosstalk Toward Thmentioning
confidence: 99%
“…Research of bladder cancer has demonstrated that angiogenesis has an important role in bladder cancer progression (19). It was demonstrated that CD31 had a strong positive expression in bladder cancer, and a weak negative expression in normal bladder tissue (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been demonstrated that the number of ECs are increased according to tumor progression and are negatively associated with the prognosis of bladder cancer (19). In the present study it was hypothesized that ECs serve other direct or indirect roles in bladder cancer apart from the known metabolism-associated roles (such as oxygen supply).…”
Section: Resultsmentioning
confidence: 99%